The notion of recognition in Hegel and its contributions to the field of nursing - Albornoz, Lucas Ignacio (2024)
The main objective of this essay is to show the theoretical contributions of the Hegelian notion of recognition (Anerkennung) in the field of nursing, referring particularly to the theme of care. To do this, we will approach the concept of recognition from the work of the German philosopher G. W. F. Hegel (1770-1831) entitled Phenomenology of the Spirit. The essay will be divided into two parts. Firstly, we will expose the Hegelian notion of recognition from Chapter IV of the Phenomenology of Spirit, dedicated to Self-consciousness. And then, secondly, we will show the importance that Hegelian theory on recognition has for some problems and challenges specific to the field of nursing. In the course of this essay we intend to show and justify that Hegel's approach to recognition allows us to philosophically, ethically and politically base the process of health care in the field of nursing, thus allowing us to achieve a more comprehensive meaning of care, this It is, not strictly reduced to the sphere of the biological, but also involving the ethical, psychological, economic and historical-political dimensions, both of those who provide care and those who receive it.